Learning Degrees for Students with Special Needs in Inclusion Class Settings - Qisthi, Aulia; Juhanaini, Juhanaini (Angstrom Centre of Education, 2024)
The aim of this study is to describe the learning degrees of students with special needs in the inclusive high school classroom setting in Pangkalpinang City. This study used a qualitative approach with the case study method which was conducted to see and observe learning for students with special needs at SMAN 1 Pangkalpinang. Data collection techniques using interviews and observation. Data analysis techniques in this study used three stages, namely data reduction, data exposure, and drawing conclusions. The results of the research are the learning degrees of students with special needs in the inclusion class setting at SMAN 1 Pangkalpinang going well because the teacher has made learning modifications according to the level of potential, obstacles, and needs of students. The teacher's attitude towards the uniqueness of the learning process of students with special needs is very positive. The teacher’s efforts in teaching students with special needs together with other students in inclusive classes include: (1) Consultation with special school teacher, (2) Discussions with colleagues, (3) Implementing cooperative learning and project based learning which accompanies all students, (4) Learning for students with special needs in inclusive classes is developed on the principles of flexibility, modification of learning degrees, and support